The Role of Health Workers in Managing Degenerative Diseases in the Elderly at the Negeri Lama Community Health Center: A Case Study - Dhyta Nurhasanah Janas; Ermi Girsang; Sri Lestari Ramadhani Nasution (The International Journal of Medical Science and Health Research, 2026)
Introduction: The increasing elderly population in Indonesia presents significant challenges in managing degenerative diseases, particularly in primary health care facilities with limited resources. This study aims to explore the role of health workers in managing degenerative diseases in the elderly at the Negeri Lama Community Health Center. Methods: This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with seven informants (elderly cluster officers, non-communicable disease program holders, doctors, pharmacists, and nutritionists), observation, and documentation. Data analysis used thematic analysis with source triangulation, method triangulation, member check, and audit trail to ensure data validity. Results: Health workers performed curative roles through integrated medical services including comprehensive examinations, diagnosis, medication provision (amlodipine, metformin, glimepiride, simvastatin, allopurinol), pharmaceutical and nutritional counseling, and referral systems. Preventive roles were implemented through routine health screenings using E-pus and P-care applications, counseling on healthy lifestyles, education on balanced nutrition, and lifestyle modifications. Challenges included complex disease complications (multimorbidity), unpredictable drug shortages from the District Health Office, limited diagnostic facilities, declining memory and cognitive function in the elderly, low health literacy, irregular visits, unstable internet networks, poor road conditions, flooding, geographical distance, and economic constraints. Communication patterns applied were patient-centered with specific adjustments for the elderly including louder volume, slower speech, simple language, and family involvement in the education process. Interprofessional collaboration involved medical records staff, elderly cluster officers, pharmacists, and nutritionists working according to standard operating procedures. Discussion: The findings align with previous research emphasizing comprehensive geriatric assessment, the effectiveness of pharmacist counseling in improving medication adherence, the importance of family support in chronic disease management, and the impact of geographical and economic barriers on healthcare access. The study highlights the need for integrated approaches addressing both clinical and social determinants of health in elderly care. Conclusion: Health workers at the Negeri Lama Community Health Center have implemented comprehensive curative and preventive roles despite various challenges. Improvements are needed in logistics management systems, development of educational media, strengthening interprofessional collaboration, innovation in education methods, and family and community support to optimize health services for the elderly with degenerative diseases.